2017
DOI: 10.1016/j.apnu.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of Adoptive Parents: A Longitudinal Mixed Methods Analysis

Abstract: As adoptive parents create a new family, they face myriad changes both pre-and post-placement of their child. The aim of this study was to describe parent perceptions and depressive symptoms during this transition via reports collected with an online survey. Using content analysis, we analyzed a total of 110 responses from 64 parents at three time points: 4–6 weeks pre-placement, and 4–6 weeks and 5–6 months post-placement. Five main themes were revealed: Transition from uncertainty to a new normal; unique exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
1
15
0
3
Order By: Relevance
“…In the current analysis, our research objectives were to (1) describe how parental expectations change across time, from pre‐ to post‐placement; (2) investigate correlations between parental expectations and depressive symptoms over time; and (3) analyze associations of those changes in expectations with additional variables through longitudinal multilevel modeling. This study was part of a larger investigation whose results are reported elsewhere (Foli, Hebdon, Lim, & South, ; Foli, South, Lim, & Hebdon, ; Foli, South, Lim, & Jarnecke, ).…”
Section: The Current Studymentioning
confidence: 91%
See 1 more Smart Citation
“…In the current analysis, our research objectives were to (1) describe how parental expectations change across time, from pre‐ to post‐placement; (2) investigate correlations between parental expectations and depressive symptoms over time; and (3) analyze associations of those changes in expectations with additional variables through longitudinal multilevel modeling. This study was part of a larger investigation whose results are reported elsewhere (Foli, Hebdon, Lim, & South, ; Foli, South, Lim, & Hebdon, ; Foli, South, Lim, & Jarnecke, ).…”
Section: The Current Studymentioning
confidence: 91%
“…This study was part of a larger investigation whose results are reported elsewhere (Foli, Hebdon, Lim, & South, 2017; Foli, South, Lim, & Hebdon, 2016; Foli, South, Lim, & Jarnecke, 2016). …”
Section: The Current Studymentioning
confidence: 92%
“…Existe evidencia sobre la incapacidad de algunos padres adoptivos para aceptar al niño real, distinto al niño idealizado 19,20 .…”
Section: Factores De Riesgo Asociados a Los Problemas De Conducta En unclassified
“…Bir çalışmada evlat edinen ailelerin doğal sağlamlıklarının olduğuna işaret edilmiştir (Foli, Hebdon, Lim and South, 2017). Başka bir çalışmada evlat edinen annelerin, doğum yapmış annelerin doğum sonrası dönemine göre, daha iyi hissettiği ve daha az psikopatolojiye sahip olduğu saptanmıştır (Mott et al, 2011).…”
Section: İstanbul Ticaret üNiversitesi Sosyal Bilimler Dergisiunclassified